1979
DOI: 10.1159/000115091
|View full text |Cite
|
Sign up to set email alerts
|

A Correlation of Clinical Findings and CT in Ischaemic Cerebrovascular Disease

Abstract: 248 patients with an ischaemic stroke were investigated with computer tomography. A hypodense lesion was observed in 18% of TIAs, 76% of PRINDS and 95% of completed stroke patients. In the patients with TIA the hypodense lesions were mainly single ones, whereas completed stroke patients also had a significantly higher proportion of more bilateral lesions. Atrophy was present in 44% of TIA patients, 68% of PRIND patients and 82% of completed stroke patients. Atrophy was generalised in 60% of the patients and ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
9
0
1

Year Published

1981
1981
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(14 citation statements)
references
References 9 publications
4
9
0
1
Order By: Relevance
“…The second most common was Posterior Cerebral Artery territory in 5 cases (10%) and close to the study by Ladurner et al (8) .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The second most common was Posterior Cerebral Artery territory in 5 cases (10%) and close to the study by Ladurner et al (8) .…”
Section: Discussionsupporting
confidence: 91%
“…The most common CT finding was an acute cortical infarction seen in 27 cases (i.e54%) and the second most common finding was lacunar infarction seen in 14 cases i.e 28% and was accordance with study done by Regli L et al 1993 (7) . Hemorrhagic stroke accounted for 3 cases i.e 6 % and was correlated to study by Ladurner G et al and Regli L et al (15-25%) who found the same finding (7,8) .…”
Section: Discussionsupporting
confidence: 84%
“…28 " 30 In cerebral haematoma, the haemorhage is immediately visible as a hyperdense area and is easy to quantify. In cerebral infarction, the lesion is seen as a hypodense area.…”
Section: Discussionmentioning
confidence: 99%
“…5 Increases in cerebrovascular resistance occur independently of intracranial pressure 6 and may limit cerebral recovery. 7 Accordingly, an effective cerebral vasodilator might have a significant impact upon the neurologic outcome follow- ing a period of complete cerebral ischemia.…”
mentioning
confidence: 99%